Comparison of Nitroglycerin and Terbutaline for External Cephalic Version in Women Who Received Neuraxial Anesthesia: A Retrospective Analysis. Issue 3 (September 2020) - Katz, D.; Riley, K.; Kim, E.; Beilin, Y.
Abstract : ( Anesth Analg . 2019. doi: 10.1213/ANE.0000000000004155) At term, about 3% to 4% of worldwide pregnancies have a fetus in the breech presentation, a common risk factor for delivery complications. The current recommendation to reduce perinatal morbidity and mortality with breech presentation is to perform a cesarean delivery. An alternative is external cephalic version, in which the fetus is manually rotated into vertex position to allow for an attempted vaginal delivery. The success rate of this procedure increases via utilization of neuraxial anesthesia, which allows for the relaxation of abdominal muscles, and via tocolytic agents which provide uterine relaxation. Two examples of such tocolytic agents are nitroglycerin and terbutaline. The authors of this study hypothesized that no difference in the successful cephalic version rate would exist between nitroglycerin and terbutaline.